The very best of dale carnegie - Carnegie, Dale (Rupa publications india New Delhi, 2018)
One of the world$1 (Bs most popular authors of self-help books, Dale Carnegie$1 (Bs bestselling works and immensely enlightening courses have helped millions improve themselves over the years. Carnegie rose to fame when he wrote about ways to overcome one of the most common fears of man: Talking in public. His advice, that has included never criticizing, complaining or condemning another person, giving sincere appreciation to others, banishing worry, developing self-confidence and so on, have great relevance for those who wish to improve themselves and their professional lives. The Man Who Transformed Lives is a comprehensive selection of Carnegie$1 (Bs five celebrated titles, including selections from the classic How to Win Friends and Influence People that has sold a million copies worldwide. This book will help you in all aspects of life, be it improving your speaking skills, developing self-confidence, a positive attitude, overcoming depression, learning how to achieve the perfect work-life balance or getting someone to like you. A tribute to one of the most prolific writers of the genre, this book is also a celebration of one life-changing idea: We can be more positive, more tenacious and more self-confident. All we have to do is try.s
index
Keywords: Achievement; Conduct of life